Age, Sex, and BMI Differences Related to Repairable Meniscal Tears in Pediatric and Adolescent Patients. Issue 2 (February 2023) - Rohde, Matthew S.; Shea, Kevin G.; Dawson, Timothy; Heyworth, Benton E.; Milewski, Matthew D.; Edmonds, Eric W.; Adsit, Elizabeth; Wilson, Philip L.; ,; Albright, Jay; Algan, Sheila; Beck, Jennifer; et al.
Background: The incidence of meniscus tears and ACL tears in pediatric patients continues to rise, bringing to question the risk factors associated with these injuries. As meniscus tears are commonly repaired in pediatric populations, the epidemiology of repairable meniscus tears is an important for consideration for surgeons evaluating treatment options. Purpose: To describe meniscal tear patterns in pediatric and adolescent patients who underwent meniscal repair across multiple institutions and surgeons, as well as to evaluate the relationship between age, sex, and body mass index (BMI) and their effect on the prevalence, type, and displacement of repaired pediatric meniscal tears. Study Design: Case series; Level of evidence, 4. Methods: Data within a prospective multicenter cohort registry for quality improvement, Sport Cohort Outcome Registry (SCORE), were reviewed to describe repaired meniscal tear patterns. All consecutive arthroscopic meniscal repairs from participating surgeons in patients aged <19 years were analyzed. Tear pattern, location, and displacement were evaluated by patient age, sex, and BMI. A subanalysis was also performed to investigate whether meniscal tear patterns differed between those occurring in isolation or those occurring with a concomitant anterior cruciate ligament (ACL) injury. Analysis of variance was used to generate a multivariate analysis of specified variables. Sex, age, and BMI results were compared across the cohort. Results: There were 1185 total meniscal repairs evaluated in as many patients, which included 656 (55.4%) male and 529 (44.6%) female patients. Patients underwent surgery at a mean age of 15.3 years (range, 5-19 years), with a mean BMI of 24.9 (range, 12.3-46.42). Of the 1185 patients, 816 (68.9%) had ACL + meniscal repair and 369 (31.1%) had isolated meniscal repair. The male patients underwent more lateral tear repairs than the female patients (54.3% to 40.9%; P < .001) and had a lower incidence of medial tear repair (32.1% vs 41.4%; P < .001). Patients with repaired lateral tears had a mean age of 15.0 years, compared with a mean age of 15.4 years for patients with repaired medial or bilateral tears ( P = .001). Higher BMI was associated with "complex" and "radial" tear repairs of the lateral meniscus ( P < .001) but was variable with regard to medial tear repairs. Conclusion: In pediatric and adolescent populations, the data suggest that the surgical team treating knees with potential meniscal injury should be prepared to encounter more complex meniscal tears, commonly indicated in those with higher BMI, while higher rates of lateral meniscal tears were seen in male and younger patients. Future studies should analyze correlates for meniscal repair survival and outcomes in this pediatric cohort undergoing knee surgery.